A novel knotless hand-sewn end-to-end anastomosis using V-loc barbed suture vs. stapled anastomosis in laparoscopic left colonic surgery: A propensity scoring match analysis - Xu, Shining; Zhao, Xuan; He, Zirui; Yang, Xiao; Ma, Junjun; Dong, Feng; Zang, Lu; Fingerhut, Abe; Zhang, Luyang; Zheng, Minhua (Frontiers in Surgery, 2022)
Background Laparoscopic colectomy is widely practiced for colon cancer, but the anastomosis method for laparoscopic colon cancer radical resection is still inconclusive, especially in the cases of left hemicolectomy. In our practice, we utilize a new knotless hand-sewing end-to-end anastomosis technique (KHEA) with barbed thread and compared the perioperative outcomes of KHEA and stapled anastomosis in our center to prove the safety and efficacy of this approach. Method We retrospectively analyzed 226 patients who underwent laparoscopic-assisted radical resection of left colon cancer with KHEA and stapled anastomosis from 2010 to 2021 at the single Center of Ruijin Hospital, Shanghai, China. The surgical details and postoperative outcomes were analysed to evaluate this technique. Result Time to finish the anastomosis (mean 7.85 versus 11.92, p<0.001) and the surgical cost (mean 46569.71 versus 50915.35, p<0.05) showed obviously differences in the KHEA group than in the stapler group. The mean bowel fonction recovery day (2.61 versus 2.71, p=0.466) and length of hospital stay (8.61 versus 7.91, p=0.407) were similar in two groups. The rate of postoperative complications also showed no evident difference. The occurrence of anastomotic leak was observed in 11 patients: 6 patients in the stapler group (7.3 %) and 5 patients in the KHEA group (12.2 %) (p>0.05). Conclusion KHEA technique is a safe and feasible anastomosis technique for laparoscopic left hemicolectomy. The KHEA technique could significantly reduce surgical cost and operational time with comparable complication rates.